2020
DOI: 10.3390/ma13163595
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization of MoS2 Atomic Layers Mechanically Exfoliated on a Si Substrate

Abstract: Mo disulfide overlayers with the thickness exceeding 1.77 nm were obtained on Si substrates through mechanical exfoliation. The resulting Mo disulfide flakes were then analyzed ex situ using combination of Auger electron spectroscopy (AES), elastic-peak electron spectroscopy (EPES) and scanning electron microscopy (SEM) in order to characterize their surface chemical composition, electron transport phenomena and surface morphology. Prior to EPES measurements, the Mo disulfide surface was sputter-cleaned and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A high‐resolution scanning Auger microprobe Microlab 350 (Thermo Electron) was employed in order to monitor the chemical composition of the MoS 2 flakes with a lateral resolution of about 50 nm and a depth information from only a few MoS 2 monolayers. [ 56 ] Differential AES spectra were recorded at 10 keV and pph signals for detected elements Si, O, C, Mo, and S were used for a qualitative and quantitative analysis of the materials (Avantage software, version 4.88). Sensitivity factors for calculation of the chemical composition were taken from the Handbook of Auger electron spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…A high‐resolution scanning Auger microprobe Microlab 350 (Thermo Electron) was employed in order to monitor the chemical composition of the MoS 2 flakes with a lateral resolution of about 50 nm and a depth information from only a few MoS 2 monolayers. [ 56 ] Differential AES spectra were recorded at 10 keV and pph signals for detected elements Si, O, C, Mo, and S were used for a qualitative and quantitative analysis of the materials (Avantage software, version 4.88). Sensitivity factors for calculation of the chemical composition were taken from the Handbook of Auger electron spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Early experimental studies of polycrystalline MoS 2 powders have shown that Mo oxide layers present on the surface form slowly and act as passivating layers till at least 100 • C [31,35]. However, freshly exfoliated single MoS 2 flakes did not show any direct manifestations of the protective oxide layers [44]. They displayed electronic density shifts within the MoS 2 above 200 • C [35].…”
Section: Phenomenological Observations Of Thermal Mos 2 Oxidation In Air and In Watermentioning
confidence: 97%